A letter of Marcus Antonius Kappus to Eusebius Franciscus Kino (Sonora in 1690) : appendix: facsimile - Tomaž Nabergoj (Acta Neophilologica, 1999)
An article with the above title was published in the last number of Acta Neophilologica (XXXI/1998, pp. 65-80), on a letter written by the Slovene Jesuit missionary, Marcus Antonius Kappus (1657-1717), in 1690, in Sonora in north-western Mexico to his superior, Eusebius Franciscus Kino. The letter is kept in Archivo Histórico de la Hacienda in Mexico City, legajo 279, expediente 19. Unfortunately, the facsimile of the published letter was ommitted during the preparation of the 1998 volume of Acta Neophilologica. Since this reproduction is an integral part of the article and is now for the first time that one Kappus' letter is preserved in original, we publish the facsimile of this letter in the present appendix.